Response of Soil Fungal Community to Drought-Resistant Ea-DREB2B Transgenic Sugarcane - Zhao, Xiaowen; Liu, Qi; Xie, Sasa; Jiang, Yuke; Yang, Huichun; Wang, Ziting; Zhang, Muqing (Frontiers in Microbiology, 2020)
Drought limits crop productivity, especially of sugarcane, which is predominantly grown in the subtropical parts of China. Soil microbes perform a wide range of functions that are important for plant productivity and responses to drought stress, and fungi play an important role in plant–soil interactions. The Ea-DREB2B gene of sugarcane, Saccharum arundinaceum, is involved in regulating the response to drought stress. In this study, fungal communities of the transgenic (TG) sugarcane variety GN18, harboring the drought-tolerance gene Ea-DREB2B and its corresponding non-TG wild-type (WT) variety, FN95-1702, were investigated in three soil compartments (rhizoplane, rhizosphere, and bulk soil) by assessing the internal transcribed spacer region using Illumina MiSeq. As the soil microbial community is also affected by various environmental factors, such as pH, carbon availability, and soil moisture, we determined the total carbon (TC), total nitrogen (TN), and total phosphorus (TP) contents in the rhizoplane, rhizosphere, and bulk soil compartments to explore the associations between soil fungal communities and host plant characteristics. Differences between the soil fungal communities of TG and WT plants were detected. The alpha diversity of TG fungal communities was more correlated to environmental factors than beta diversity. The abundance of OTUs enriched in TG root-related area was far more than that in the root-related area of WT plants. Thereinto, more saprotrophs were enriched in TG root-related area, indicating altered niches of fungal guilds around TG roots. These results revealed that host plant genotype did play a key role for strengthening plant-fungi interaction and enhancing beneficial fungal function in root-related area (rhizoplane and rhizosphere) of TG sugarcane in order to response to drought stress.